2018
DOI: 10.1001/jamacardio.2018.1827
|View full text |Cite
|
Sign up to set email alerts
|

Association of APOL1 With Heart Failure With Preserved Ejection Fraction in Postmenopausal African American Women

Abstract: Status as a carrier of a high-risk APOL1 genotype was associated with HFpEF hospitalization among postmenopausal women, which is partly accounted for by baseline kidney function. These findings do not support an association of high-risk APOL1 genotypes with coronary heart disease, stroke, or mortality in postmenopausal African American women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 47 publications
2
11
0
Order By: Relevance
“…It is possible that blood pressure differences do exist between those with and without APOL1 risk alleles with more severe hypertension, or in those with overt kidney disease. Similar to other studies [32], a significant difference was found in baseline kidney function measured by serum creatinine and eGFR in those with two APOL1 risk alleles, without significant differences detected in baseline albuminuria. Although much research has focused on the podocyte as a site of APOL1-induced injury, a difference in eGFR occurring without albuminuria suggests the mechanism of renal disease may not limited to the glomerulus or may affect the glomerulus in patterns beyond classic focal segmental glomerulosclerosis [33].…”
Section: Discussionsupporting
confidence: 88%
“…It is possible that blood pressure differences do exist between those with and without APOL1 risk alleles with more severe hypertension, or in those with overt kidney disease. Similar to other studies [32], a significant difference was found in baseline kidney function measured by serum creatinine and eGFR in those with two APOL1 risk alleles, without significant differences detected in baseline albuminuria. Although much research has focused on the podocyte as a site of APOL1-induced injury, a difference in eGFR occurring without albuminuria suggests the mechanism of renal disease may not limited to the glomerulus or may affect the glomerulus in patterns beyond classic focal segmental glomerulosclerosis [33].…”
Section: Discussionsupporting
confidence: 88%
“…We noted that the APOL1 high‐risk genotypes were not associated with an increased risk for all‐cause mortality. This is in line with findings from the African American Study of Kidney Disease and Hypertension (AASK; mean age = 54 years), the Women's Health Initiative (mean age = 62 years), and the Systolic Blood Pressure Intervention Trial (mean age about 64 years), all of which reported a lack of association between APOL1 and all‐cause mortality 23‐25 . In contrast, the CHS (mean age about 74 years) reported a borderline increased risk for total mortality associated with the APOL1 high‐risk genotypes (adjusted HR = 1.3; 95% CI = 1.0–1.7; P = .05), 14 whereas the African American Diabetes Heart Study (mean age about 56 years) reported a survival advantage associated with the APOL1 risk variants 26 .…”
Section: Discussionsupporting
confidence: 80%
“…Apolipoprotein L1 (APOL1) is located at chromosome 22q12.3 and APOL1 gene encodes a trypanolytic factor that dissolves pathogenic Trypanosoma brucei subspecies in humans and gorillas ( 28 ). Other studies have shown a link between non-diabetic nephropathy and variations in the APOL1 gene ( 29 , 30 ), which are also associated with atherosclerosis ( 31 ). APOL1 is one of six genes of the APOL gene family, which are a set of genomic hotspots for various diseases ( 32 ), including schizophrenia, cancer and chronic kidney disease ( 33 , 34 ).…”
Section: Introductionmentioning
confidence: 99%